A DAILY CO2 CONCENTRATION IN NORTHERN SURABAYA CITY - Magita, Nastiti Sigra Dewi; Muzayanah, Muzayanah; Budiyanto, Eko (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2022)
CO2 concentration is one air quality parameter set by WHO. High concentrations of carbon dioxide will have an impact on human health. CO2 is a gas that can cause a greenhouse effect in a city like Surabaya. This study aims to reveal the dynamics of CO2 concentration in northern Surabaya, which is a center of urban activity in Surabaya. This type of research is descriptive analytic with a quantitative approach. The population used is based on the division of administrative regions in Surabaya u tara section. Sampling is carried out in a purposive way, where each land use is taken five locations. Data collection techniques use measurement and observation. The data analysis technique used is descriptive. The results of the data analysis showed that there was a difference in the average CO2 concentration in the morning and evening. All research sites have CO2 concentrations above the safe threshold of CO2 concentrations set by WHO. There is an increase in CO2 concentrations in the morning and evening variably. The average CO2 concentration in the morning was recorded at 436.05 ppm and increased at night to 518 ppm. The highest CO2 concentration in the morning occurred on Colombo road at 467 ppm and the lowest at 345 ppm on Bangunsari road. The highest average CO2 concentration at night occurred on Morokrembangan road, which was 558 ppm and the lowest on Bangunsari road was 460 ppm. Keywords: CO2 concentration, air pollution, northern Surabaya